2010
DOI: 10.1080/19768351003765145
|View full text |Cite
|
Sign up to set email alerts
|

CHIP promotes the degradation of mutant SOD1 by reducing its interaction with VCP and S6/S6′ subunits of 26S proteasome

Abstract: Previously we showed that CHIP, a co-chaperone of Hsp70 and E3 ubiquitin ligase, can promote the degradation of mutant SOD1 linked to familial amyotrophic lateral sclerosis (fALS) via a mechanism not involving SOD1 ubiquitylation. Here we present evidence that CHIP functions in the interaction of mutant SOD1 with 26S proteasomes. Bag-1, a coupling factor between molecular chaperones and the proteasomes, formed a complex with SOD1 in an hsp70-dependent manner but had no direct effect on the degradation of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In a previous study, we found that VCP/p97 (referred to as transitional endoplasmic reticulum ATPase) was recovered in mutant SOD1-rich aggregates from the spinal cord in the G93A SOD1 mouse model, already at a presymptomatic stage of the disease (28). Possibly, VCP/p97, which interacts directly or indirectly with misfolded mutant SOD1 (55, 56), is sorted with it into exosomes as unwanted material to be shuttled out of astrocytes. VCP/p97 mutations have been associated with familial and sporadic ALS cases (57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that VCP/p97 (referred to as transitional endoplasmic reticulum ATPase) was recovered in mutant SOD1-rich aggregates from the spinal cord in the G93A SOD1 mouse model, already at a presymptomatic stage of the disease (28). Possibly, VCP/p97, which interacts directly or indirectly with misfolded mutant SOD1 (55, 56), is sorted with it into exosomes as unwanted material to be shuttled out of astrocytes. VCP/p97 mutations have been associated with familial and sporadic ALS cases (57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the ALS-related SOD1 mutant binds directly to the S6 (Rpt3/PSMC4) and S6′(Rpt5/PSMC3) subunits of the 19S regulatory complex of the proteasome and interferes with their normal functions. Since both S6 and S6′ subunits belong to the AAA ATPase superfamily, it has been suggested that the association between these ATPase subunits and the mutant SOD1 proteins impairs the ATPase-induced activation of the 20S catalytic core and causes proteasomal dysfunction and degradation stalling (128). Moreover, the SOD1 mutant interacts physically with the co-chaperone CHIP (carboxyl terminus of Hsc70 interacting protein) (129, 130) and with the ubiquitin-binding proteins Bag1 and VCP (valosin-containing protein; p97) (128).…”
Section: Interaction Partners Of Mutant Sod1 and Their Toxic Propertiesmentioning
confidence: 99%
“…Since both S6 and S6′ subunits belong to the AAA ATPase superfamily, it has been suggested that the association between these ATPase subunits and the mutant SOD1 proteins impairs the ATPase-induced activation of the 20S catalytic core and causes proteasomal dysfunction and degradation stalling (128). Moreover, the SOD1 mutant interacts physically with the co-chaperone CHIP (carboxyl terminus of Hsc70 interacting protein) (129, 130) and with the ubiquitin-binding proteins Bag1 and VCP (valosin-containing protein; p97) (128). Interestingly, CHIP and VCP compete with each other for the binding to SOD1 mutant, indicating that the chaperone complex (CHIP/Hsp70) and the proteolytic machinery (VCP/26S proteasome) compete for the common substrate SOD1 mutant (128).…”
Section: Interaction Partners Of Mutant Sod1 and Their Toxic Propertiesmentioning
confidence: 99%
“…It mediates polyubiquitination of Hsp70/Hsc70, which preferentially promotes degradation of SOD1 via 26S proteasome, as shown in Figure 5B (Urushitani et al, 2004 ). The overexpression of CHIP decreases cytotoxicity in cultured human cells by reducing levels of mutant SOD1 together with Hsp70/Hsc70 and Hsp90 (Choi and Lee, 2010 ). The degradation of mutant SOD1 protein through autophagy is carried out by Bag3/HspB8/Hsc70/CHIP complex that inserts mutant protein into autophagosome (Crippa et al, 2010 ).…”
Section: Chip a Molecule Associated With Multiple Neurodegenerative mentioning
confidence: 99%